2017
DOI: 10.1097/md.0000000000007072
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted

Abstract: Objective:This meta-analysis aimed to perform a meta-analysis including randomized controlled trials (RCTs) to assess the efficiency and safety of tranexamic acid (TXA) for reducing blood loss and transfusion requirements in patients undergoing open myomectomy.Methods:A systematic search was performed in Medline (1966–2017.03), PubMed (1966–2017.03), Embase (1980–2017.03), ScienceDirect (1985–2017.03,) and the Cochrane Library. Study evaluated the efficiency and safety of TXA in myomectomy was selected. Meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…Accordingly, patients who received TXA had significantly higher postoperative haemoglobin concentrations when compared to the placebo group. This was similar to the observation by Wang et al [25] that tranexamic acid reduced the need for blood transfusion during myomectomy. The observed ability of tranexamic acid to reduce total blood loss associated with myomectomy, improve postoperative haemoglobin concentration, and reduce the risk of blood transfusion requirements was probably due to its ability to inhibit enzymatic breakdown of fibrins in blood clots by inhibiting the activation of plasminogen to plasmin [15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Accordingly, patients who received TXA had significantly higher postoperative haemoglobin concentrations when compared to the placebo group. This was similar to the observation by Wang et al [25] that tranexamic acid reduced the need for blood transfusion during myomectomy. The observed ability of tranexamic acid to reduce total blood loss associated with myomectomy, improve postoperative haemoglobin concentration, and reduce the risk of blood transfusion requirements was probably due to its ability to inhibit enzymatic breakdown of fibrins in blood clots by inhibiting the activation of plasminogen to plasmin [15].…”
Section: Discussionsupporting
confidence: 91%
“…The differences in findings might be due to differences in patients' characteristics across the regions where the studies took place. Also, in this study, tranexamic acid infusion reduced the mean operative time by about 30 minutes, a finding similar to what was reported by Wang et al [25]. This is because a clear operative field reduces the need to mop blood from the operating field, thus allowing for minimal interruption of the procedure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, we found a significant reduction in hospital stay in the case group compared to the control group (p value =0.001), and we found a significant reduction in postoperative Hb levels in the control group and a decreased need for blood transfusions in the case group. These differences were statistically significant and were confirmed by other studies, which showed the advantageous role of tranexamic acid in reducing blood loss and Hb levels following surgery and hospital stay, as well as in facilitating blood transfusion in patients who underwent open myomectomy with iv tranexamic acid at the time of skin incision (Caglar et al, 2008, Wang et al, 2017, Shaaban et al, 2016.…”
Section: Discussionsupporting
confidence: 76%
“…The article, “The efficiency and safety of tranexamic acid for reducing blood loss in open myomectomy, A meta-analysis of randomized controlled trials”, [ 1 ] which appeared in Volume 96, Issue 23 of Medicine , is being retracted for errors in the data collection. The errors affected the results and conclusion of the paper.…”
mentioning
confidence: 99%